PENDEKATAN SISTEM DALAM PEMBENTUKAN PERATURAN DAERAH - I WAYAN SUANDI (Fakultas Hukum Universitas Udayana, 2008)
Systemic approach is relevant to the process of formulating of regional rule. The unity of departments that are interrelation and interdependency like the Regional House of Representativesand District Head causes the implementation of regional rule becomes more efficient. The regional rule must be in accordance with condition of community where it will be hold. Therefore, the regional rule maker must understand the interests what is growing and developing in community.Besides that, with paying attention to an input from the members of community can grow sense of belonging and morality duty of them to obey the regional rule. In order to be achieve its goal, the systemic approach must be completed by a control like feedback so that, the relation of input, process and output become balance and dynamic.